A promising opportunity in HIV/AIDS intervention? : the men as partners programme and its lessons for a wider gender interpretation in HIV/AIDS intervention in Southern Africa - Van Vliet, Mirjam (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2007.